Language Choice in English Language Teaching at AKPARTA Surakarta - Eka Susylowati (Universitas Musamus, 2021)
Language choice is an important in a sociolinguistics study. It is affected by social differences of the participants, seting, and topics, etc. This study is aimed to describe language choice in English language teaching at Akparta Surakarta. The data source of this research is conversation of teacher and student, student and student in the classroom. The method used was descriptive-qualitatif method. The result of the study finds that standard language and non-standard language used in English language teaching in Akparta Surakarta to communicate between the teacher and student, student and student. There are several factors that affect the language choice, such as participant, setting, topics, and purpose of the speaking.